Sistema silvipastoril na melhoria do bem-estar de bovinos de corte - Baliscei, Marcio Antonio (2011)
There were evaluated the microclimate and feeding behavior of 24 Zebu steers in a system without shadow (SS) and silvopastoral (SP) with eucalyptus in summer and winter, maintained in star grass (Cynodon plectostachyus), with an average of 18 months and live weight of 294.5 kg. The variables measured were air temperature (Ta), black globe (Bt), relative humidity (RH), wind speed (Ws), at every 2 hours for 24 hours (between rows and in the shadow (SP) and no effect shade (SS)). For the observation of behavior, it was used a completely randomized design with two season, two treatments, twenty-four hours and twelve repetitions. The observations were carried out for 24 hours for three days, every 15 minutes. For the observations of the microclimate, the design was a randomized blocks (months) in plots (system), the subplot (hours) and the sub-subplot (season). The grazing behavior (PAST) and lying ruminating (RUDEIT) were influenced by the hour with a maximum of 52.1% for PAST and minimum of 12.3% for RUDEIT, both at 14h. The behavior lying idle (OCDEIT) was influenced by hours and season, being a minimum value of 11.6% at 14h in summer (23.9%) and winter (13.9%). Standing ruminating (RUEMP) without effect of hour, suffered interaction of season x system, being 9.43 and 6.19% (summer), and 4.36 and 8.27% (winter), respectively, for SP and SS. Standing idle (OCEMP) was affected by the hour, with maximum 15.8% at 14h, and interaction system x season, being 20.10 and 8.82% (summer), and 9.05 and 8.44% (winter), respectively, for SP and SS. The SP system has changed the environment affecting the time of RUEMP and OCEMP. With the exception of Ta and RH, the Bt (24.73 and 26.41ºC), Ws (3.16 and 4.57 m s-1), BGHI (71.83 and 73.84), HLI (74.53 and 76.11) and RTL (526 , 46, and 595.80 W m-2), respectively, for SP and SS were higher in SS. Ta, RH and Ws, had a quadratic effect of hour of day. With effect of station the Ta (27.55, 14.93oC), UR (72.11, 60.68%), Bt (29.80, 21.33oC), BGHI (80.04, 65.63), HLI (81.64, 69.00) and RTL (575.65, 546.61 W m-2), respectively, in summer and winter. Bt, RH and RTL, suffered an interaction of season x time, and quadratic effect, the RTL showed an interaction of system x season. Bt was correlated with BGHI (0.962), HLI (0.956) and RTL (0.809). Silvopastoral system decreased the Bt and Ws, and made more harmonious environment by decreasing the climatic differences between seasons.